Serum cold-inducible RNA-binding protein (CIRP) levels as a prognostic indicator in patients with acute ischemic stroke - Li, Mingming; Yao, Min; Shao, Kangmei; Shen, Xueyang; Li, Yongnan; Ge, Zhaoming (Frontiers in Neurology, 2023)
Background: Acute ischaemic stroke (AIS) is the leading cause of morbidity and mortality among cerebrovascular diseases. While animal studies have suggested a correlation between cold-inducible RNA -binding protein (CIRP) serum levels and the severity and prognosis of cerebral infarction, there has been a lack of research exploring this association in humans with cerebral infarction.2 This is a provisional file, not the final typeset article Materials and Methods: A total of 148 patients diagnosed with AIS within 7 days from symptom onset were included in the study. Comprehensive information regarding the patients' basic demographics, medical history, clinical parameters, the severity of cerebral infarction, and serum CIRP levels was collected. Follow-up data were obtained through telephonic interviews or by reviewing clinical notes for 3 months after the patients were discharged to assess the functional outcomes of treatment.Results: Our findings demonstrated a significant increase in serum CIRP levels during the early stages of AIS, followed by a gradual decline after 3 days. Significant differences were observed in the serum CIRP levels between the 1-day group and the 4-7 day group (P <0.0047), as well as between the 2-3 day group and the 4-7 day group (P <0.0006). Moreover, a significant positive correlation was observed between the serum CIRP levels and the severity of cerebral infarction. Higher serum CIRP levels were associated with more severe National Institutes of Health Stroke Scale scores (P <0.05) and larger cerebral infarction volumes (P <0.05). Furthermore, patients with higher serum CIRP levels exhibited poorer modified Rankin scale scores (P <0.05). These findings indicate that serum CIRP serves as an essential pro-inflammatory mediator and a valuable biomarker for assessing brain injury in patients with AIS.The findings of our study suggest an elevation in serum CIRP levels among patients with AIS. These levels are positively correlated with the severity of AIS and serve as indicators of a poor prognosis. Therefore, CIRP could serve as a target for early clinical intervention while managing AIS, and further research should explore serum CIRP levels as prognostic indicators in AIS.